The Newspaper Russkaia Muzykal'naia Gazeta’s Publishing Activities during World War I - Natalia V. Logacheva (RUDN Journal of Russian History, 2023)
Through their work, the author conducts a content analysis of the materials of the “Russkaia muzykal'naia gazeta” between 1914-1918, a newspaper which served as the mouthpiece of Russian cultural figures in the early 20th century, and a periodical which reflected the events of World War I both in military territories on the frontline and in the rear. The article shows from various points the development of musical culture during the First World War, not only in the two capitals - St. Petersburg and Moscow, but also in the provinces. The attitude of the Russian musical intelligentsia to the war is analyzed in the text. Specific examples provided by the author show the high level of patriotism of Russian musicians and the attitude of Western European musicians to the events of the period. In addition, there is emphasis on the influence of patriotic sentiments on the work of Russian musicians including their awareness of the role of musical culture in uniting the people and providing spiritual support to the Russian army.